Selenium- and Tellurium-Based Antioxidants for Modulating Inflammation and Effects on Osteoblastic Activity - Xi Lu; Gemma Mestres; Vijay Pal Singh; Pedram Effati; Jia-Fei Poon; Lars Engman; Marjam Karlsson Ott (MDPI AG, 2017)
Increased oxidative stress plays a significant role in the etiology of bone diseases. Heightened levels of H2O2 disrupt bone homeostasis, leading to greater bone resorption than bone formation. Organochalcogen compounds could act as free radical trapping agents or glutathione peroxidase mimetics, reducing oxidative stress in inflammatory diseases. In this report, we synthesized and screened a library of organoselenium and organotellurium compounds for hydrogen peroxide scavenging activity, using macrophagic cell lines RAW264.7 and THP-1, as well as human mono- and poly-nuclear cells. These cells were stimulated to release H2O2, using phorbol 12-myristate 13-acetate, with and without organochalogens. Released H2O2 was then measured using a chemiluminescent assay over a period of 2 h. The screening identified an organoselenium compound which scavenged H2O2 more effectively than the vitamin E analog, Trolox. We also found that this organoselenium compound protected MC3T3 cells against H2O2-induced toxicity, whereas Trolox did not. The organoselenium compound exhibited no cytotoxicity to the cells and had no deleterious effects on cell proliferation, viability, or alkaline phosphatase activity. The rapidity of H2O2 scavenging and protection suggests that the mechanism of protection is due to the direct scavenging of extracellular H2O2. This compound is a promising modulators of inflammation and could potentially treat diseases involving high levels of oxidative stress.